REPRESENTASI SOSOK AUTISM SPECTRUM DISORDER PADA DRAMA KOREA EXTRAORDINARY ATTORNEY WOO - Aulia Nurhidayah (2023)
This research was motivated by the problem of Autism Spectrum Disorder being a sensitive issue in the community. Including when the character in this figure is portrayed differently from previous films. This study aims to analyze the representation of the figure of Autism Spectrum Disorder in the Korean Drama Extraordinary Attorney Woo. This drama tells the story of a smart lawyer who has Autism Spectrum Disorder. This study used Charles Sanders Peirce's Semiotics to look at the meaning of icons, indexes, and symbols. This study used a descriptive qualitative approach using primary data sources and secondary data. Then, this research is verified through data validity techniques. The results of the research findings show that the figure of Autism Spectrum Disorder is represented as a figure who is intelligent, passionate, responsible, has credibility, can be trusted as a lawyer and can provide education and moral life to the community. In addition, this study also resulted in the discovery of discrimination, rejection, and hatred of the community towards the figure of Autism Spectrum Disorder. The conclusion of the study features characters, stories, and atmospheres that represent the dimensions of icons. Indices represent the causal relationships of icons and symbols. Whales and dolphins are symbols of the intelligence and spirit of the characters of Autism Spectrum Disorder in this drama. In addition, the symbol is also represented by non-verbal behavior in the scenes of the Korean drama Extraordinary Attorney Woo.